2008
DOI: 10.1016/j.juro.2008.04.076
|View full text |Cite
|
Sign up to set email alerts
|

Directed Differentiation of Bone Marrow Derived Mesenchymal Stem Cells Into Bladder Urothelium

Abstract: Purpose We have previously reported that embryonic rat bladder mesenchyma has the appropriate inductive signals to direct pluripotent mouse embryonic stem cells toward endodermal derived urothelium and develop mature bladder tissue. We determined whether nonembryonic stem cells, specifically bone marrow derived mesenchymal stem cells, could serve as a source of pluripotent or multipotent progenitor cells. Materials and Methods Epithelium was separated from the mesenchymal shells of embryonic day 14 rat bladd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 17 publications
1
33
0
2
Order By: Relevance
“…After being cocultured with urothelium, or cultured using urothelium-derived conditioned medium, human BMSCs express urothelium-specific genes and proteins (Tian et al 2009). The results obtained by Anumanthan et al (2008) support the concept that the embryonic bladder mesenchyma is a potent inductor that can regulate the differentiation of bone marrow MSCs into bladder urothelial cells (morphogenesis and cytodifferentiation).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…After being cocultured with urothelium, or cultured using urothelium-derived conditioned medium, human BMSCs express urothelium-specific genes and proteins (Tian et al 2009). The results obtained by Anumanthan et al (2008) support the concept that the embryonic bladder mesenchyma is a potent inductor that can regulate the differentiation of bone marrow MSCs into bladder urothelial cells (morphogenesis and cytodifferentiation).…”
Section: Discussionsupporting
confidence: 70%
“…They also expressed keratin, providing biochemical evidence of urothelial differentiation. Compared with the approaches designed by Tian et al (2009) and Anumanthan et al (2008), our model offers a simple and clear method for the culture and observation of double layer cells. The influence of contaminating smooth muscle cells and fibroblasts was minimized by removing tissue-derived epithelial cells and replating them into 6-well plates.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the case of bladder, nonhuman marrow stem cells are commonly used in differentiating into SMCs and urothelium. 5,11 The optimal approaches to induce human BMSCs to differentiate into bladder SMCs, and to a more urothelial differentiation, are still under investigation. It is known that cells release cytokines to neighboring tissues, which can modulate the fate of adjacent cells via paracrine signaling.…”
Section: Introductionmentioning
confidence: 99%
“…The possible mechanisms underlying the clinical effects are not clear. Although MSCs have the potential capacity to differentiate into bladder urothelium and donor DNA could be demonstrated in the bladder tissue at autopsy [17,18], conflicting data regarding the ability of MSCs to engraft and the response speed indicate that there is weak direct MSC-mediated tissue repair. On the other hand, the lack of a clear treatment benefit in patients with LO-HC and acute GVHD (1 patient's LO-HC but not GVHD responded, 1 patient without GVHD also responded) suggests that the mechanism might be, at least, partly different for MSCs in GVHD where they are believed to suppress GVHD by secretion of soluble anti-inflammatory factors and direct cell-to-cell contact with alloreactive T cells [11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical trials have shown encouraging results using MSCs in the management of refractory GVHD and for engraftment promotion of hemopoietic cells in a non-HLA-restricted manner [13,14,15], but limited data are focused on the use of MSCs in patients with HSCT-induced tissue toxicity, like severe LO-HC [16,17]. Since, MSCs possess the potential capacity to directly differentiate into bladder urothelium [18] or indirectly stimulate tissue repair via paracrine effects in addition to the ability to modulate acute GVHD, an important pathogenic contributor to HC, the administration of MSCs might be a feasible new treatment option for HC patients. In a pilot study, a rapid, dramatic response was observed after MSC infusion in 8 of 12 patients with gross hematuria [17].…”
Section: Introductionmentioning
confidence: 99%